Online Teaching During COVID-19: An Analysis of Changing Self-Efficacy Beliefs - Forgie, Julia; Wang, Marguerite; Dack, Lisa Ain; Schreiber, Miranda (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2024)
This quantitative study investigated teachers’ self-efficacy for teaching online compared to teaching in-person during the COVID-19 pandemic. Teacher self-efficacy is a significant predictor of both teacher practice and student outcomes. During the pandemic, teachers were forced to suddenly shift their teaching online and as a result, many new challenges were faced. Teachers from three teaching contexts (public, private, and virtual public schools) in Ontario, Canada completed the Ohio State Teacher Efficacy Scale (OSTES) and questionnaires measuring online teaching experience and training in May–June 2020 (phase 1) and again one year later, in May–June 2021 (phase 2). Results indicated that while the perceived self-efficacy of teachers improved over the course of the study, specifically in classroom management and student engagement, their perceived self-efficacy did not reach the levels reported for self-efficacy for in-person teaching, highlighting the persisting limitations educators experience in online learning environments. Additionally, efficacy for instructional strategies had not significantly increased by phase 2, indicating a particular need of targeted instruction for future teacher education programs. These results offer insights into the kind of experience and tools teacher education programs can extend to enhance teacher preparedness, and the conditions that best encourage improvements in self-efficacy for in-service teachers.